Characterization of the phenotypic variability in Colombian weedy rice (Oryza spp.). Issue 4 (July 2019) - Hoyos, Veronica; Plaza, Guido; Caicedo, Ana L.
Abstract: Weedy rice ( Oryza spp.) is considered one of the main weeds in cultivated rice ( Oryza sativa L.) around the world, having a great impact on both yield and quality of crop rice. Recent studies have characterized the range of morphological and genetic diversity in weedy rice from different locations and have revealed that there is often great morphological diversity within growing regions. No systematic attempt to characterize phenotypic diversity of weedy rice in Colombia, where this group of weeds greatly affects rice production, has yet been carried out. This study seeks (1) to establish the range of variation in various morphological characters for weedy rice collected in the five production zones of Colombia and to compare these with commercial varieties and landraces sown in the country, (2) to determine the association between weedy rice morphotypes and rice production areas in the country, and (3) to assess whether any association exists between morphology and recently discovered genetic groupings for weedy rice in Colombia. Based on a sampling of rice production areas in Colombia and evaluation of 27 phenotypic traits, a two-step cluster analysis identified four morphological groups for weedy rice in Colombia. These groupings had some limited association with geography and the genetic ancestries of weedy rice. Clustering showed that awn and apiculus color and awn length and presence are the most important predictors in defining morphological groupings. Understanding and classifying the morphological diversity may be helpful in understanding weedy rice origins, evolution, and potential management practices.